Development of a Rapid Point-of-Use DNA Test for the Screening of Genuity® Roundup Ready 2 Yield® Soybean in Seed Samples. (26th May 2016) - Chandu, Dilip; Paul, Sudakshina; Parker, Mathew; Dudin, Yelena; King-Sitzes, Jennifer; Perez, Tim; Mittanck, Don W.; Shah, Manali; Glenn, Kevin C.; Piepenburg, Olaf
Abstract : Testing for the presence of genetically modified material in seed samples is of critical importance for all stakeholders in the agricultural industry, including growers, seed manufacturers, and regulatory bodies. While rapid antibody-based testing for the transgenic protein has fulfilled this need in the past, the introduction of new variants of a given transgene demands new diagnostic regimen that allows distinguishing different traits at the nucleic acid level. Although such molecular tests can be performed by PCR in the laboratory, their requirement for expensive equipment and sophisticated operation have prevented its uptake in point-of-use applications. A recently developed isothermal DNA amplification technique, recombinase polymerase amplification (RPA), combines simple sample preparation and amplification work-flow procedures with the use of minimal detection equipment in real time. Here, we report the development of a highly sensitive and specific RPA-based detection system for Genuity Roundup Ready 2 Yield (RR2Y) material in soybean ( Glycine max ) seed samples and present the results of studies applying the method in both laboratory and field-type settings.